Combination of diabetes mellitus and lack of habitual physical activity is a risk factor for functional disability in Japanese. Issue 1 (24th January 2020) - Fujihara, Kazuya; Matsubayashi, Yasuhiro; Harada Yamada, Mayuko; Kitazawa, Masaru; Yamamoto, Masahiko; Kaneko, Masanori; Kodama, Satoru; Yahiro, Takuya; Tsutsui, Ayumu; Kato, Kiminori; Sone, Hirohito
Abstract : Objective: Declining healthy life expectancy due to functional disability is relevant and urgent because of its association with decreased quality of life and also for its enormous socioeconomic impact. The aim of this study is to examine the impact of diabetes, hypertension, dyslipidemia and physical activity habits on functional disability among community-dwelling Japanese adults. Research design and methods: This is a population-based retrospective cohort study including 9673 people aged 39–98 years in Japan (4420, men). Functional disability was defined as a condition meeting Japan's new long-term care insurance certification requirements for the need of assistance in the activities of daily living whether by caregivers or assistive devices. Cox proportional-hazards regression model identified variables related to functional disability. Results: Median follow-up was 3.7 years. During the study period, 165 disabilities occurred in the overall study population. Multivariate analysis showed that diabetes (HR 1.74 (95% CI 1.12 to 2.68)) and no physical activity habit (HR 1.83 (1.27 to 2.65)) presented increased risks for disability. HR for disability increased with the number of risk factors (HR of individuals with four conditions, 3.96 (1.59 to 9.99) vs individuals with none of those conditions as a reference). HR for disability among patients with diabetes with and without a physical activity habit was 1.68 (0.70 to 4.04) and 3.19 (1.79 to 5.70), respectively, compared with individuals without diabetes with a physical activity habit. Conclusions: The combination of diabetes and lack of habitual physical activity is predictive of functional disability in Japanese. Habitual physical activity attenuates the risk of functional disability in patients with diabetes.